2012
DOI: 10.1103/physreve.85.031101
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement entropy in Suzuki-Trotter decomposition of spin systems

Abstract: In quantum spin chains at criticality, two types of scaling for the entanglement entropy exist: one comes from conformal field theory (CFT), and the other is for entanglement support of matrix product state (MPS) approximation. On the other hand, the quantum spin-chain models can be mapped onto two-dimensional (2D) classical ones by the Suzuki-Trotter decomposition. Motivated by the scaling and the mapping, we introduce information entropy for 2D classical spin configurations as well as a spectrum, and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…Since this relation successfully explains the numerical result in a wide range of », we think that it is a correct asymptotic form of S rather than the naive logarithmic dependence proposed in Ref. 5. The snapshot spectrum may be a different concept from the entanglement spectrum in the quantum system, although our motivation originally came from the entanglement for the quantum system.…”
Section: Summary and Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Since this relation successfully explains the numerical result in a wide range of », we think that it is a correct asymptotic form of S rather than the naive logarithmic dependence proposed in Ref. 5. The snapshot spectrum may be a different concept from the entanglement spectrum in the quantum system, although our motivation originally came from the entanglement for the quantum system.…”
Section: Summary and Discussionmentioning
confidence: 73%
“…(20) shows the correct asymptotic behavior of the snapshot entropy, rather than the naive logarithmic behavior proposed in Ref. 5. As » approaches N, the theoretical curve deviates from the numerical result.…”
Section: Snapshot Entropymentioning
confidence: 68%
See 1 more Smart Citation
“…þ 1Þ is the finiteentanglement scaling exponent, and is the matrix dimension [35][36][37]. It has been shown that the correlation length is given by ¼ .…”
Section: Introductionmentioning
confidence: 99%
“…For two-dimensional (2D) classical spin systems, very recently, a similar but different idea of the quantum entanglement was proposed for classical MC; a snapshot spectrum and snapshot entropy were defined for the singular value spectrum of a snapshot generated by a MC simulation. [13][14][15] It was shown that the snapshot spectrum gave hierarchical decomposition of snapshot images in Ref. [13], and a characteristic behavior of a snapshot entropy was also observed.…”
Section: Introductionmentioning
confidence: 99%